The Spiritual Values of Islamic Economics in Tasawuf Modern: Scrutinizing the Work of Haji Abdul Malik Karim Amrullah (Hamka) - Hakim, Rahmad; Fanani, Ahmad (IAIN Surakarta, 2021)
Islamic economics has existed since the start of Islamic civilization. However, Islamic economic thoughts established by Indonesian scholars are limited. This exploratory research was carried out to determine the spiritual values of Islamic economics on Hamka's works entitled Tasawuf Modern. Primary and secondary data were collected from Hamka's works entitled Tasawuf Modern and from several papers or books that are relevant to the focus of the research. The data collected were analyzed by combining topics relevant to Islamic economics in modern Sufism and other secondary sources. Content analysis was used for data analysis. The results of this study revealed that, according to Hamka, the richest people are those that need the least. The true wealth lies in the contentment of the soul (qana'ah). Good wealth represents virtue and prohibiton for extravagancy and excessive consumerism. Further, humans need to be in between to carry out good deeds. The results of this study contribute to enriching the discourse of Islamic economic thought, especially in Islamic economic ethics and the role of ethics in business.